Strikes and Revolution in Russia, 1917. - Koenker, Diane P. (Princeton University Press, 2014)
More than seventy years since the Bolsheviks came to power, there is still no comprehensive study of workers' activism in history's first successful workers' revolution. Strikes and Revolution in Russia, 1917 is the first effort in any language to explore this issue in both quantitative and qualitative terms and to relate strikes to the broader processes of Russia's revolutionary transformation. Diane Koenker and William Rosenberg not only provide a new basis for understanding essential elements of Russia's social and political history in this critical period but also make a strong contribu.
Keywords: Strikes and lockouts -- Russia -- History -- 20th century.; Soviet Union -- History -- Revolution, 1917-1921.; Grèves et lock-out -- Russie -- Histoire -- 20e siècle.; URSS -- Histoire -- 1917-1921 (Révolution); HISTORY -- Europe -- Russia & the Former Soviet Union.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Strikes and lockouts; Russia; Soviet Union; 1900-1999; History